Development of a Web-Based Mindfulness Program for People With Multiple Sclerosis: Qualitative Co-Design Study - Sesel, Amy-Lee; Sharpe, Louise; Beadnall, Heidi N; Barnett, Michael H; Szabo, Marianna; Naismith, Sharon L (JMIR Publications, 2021)
BackgroundMindfulness-based stress reduction is an efficacious treatment for people with chronic health problems; however, it is highly intensive and time-consuming, which is a barrier for service provision. ObjectiveThis study aims to develop an internet-delivered adapted version of mindfulness-based stress reduction for people with multiple sclerosis to make the intervention more accessible. MethodsWe co-designed a web-based mindfulness program with end users, that is, people with multiple sclerosis (N=19). Iterative feedback was also collected from a subsample of the initial group of end users (n=11), and the program was reviewed by experts (n=8). ResultsWe identified three main themes common to people with multiple sclerosis: dealing with uncertainty and fears for the future, grief and loss, and social isolation. These themes were incorporated into narratives throughout the program. People with multiple sclerosis who reviewed the program gave feedback that the program was relatable, feasible, and acceptable. Experts agreed that the program appropriately represented the main tenets of mindfulness. Iterative feedback was used to further refine the program. ConclusionsThe web-based mindfulness program that we developed was viewed positively by both experts and end users. The program reflects common concerns for people with multiple sclerosis and has the potential to meet important unmet psychological needs. A randomized controlled trial was planned to determine the efficacy of the program.